Anteseden Brand Loyalty pada Produk Milo - Nafisya Eghie Rachmawaty; Salsabila Budiansah; Sri Vandayuli Riorini (Syntax Corporation, 2023)
This study aims to test and analyze Brand Loyalty Antecedents on Milo Products. The sample used in this study were consumers of Milo products. The number of data in this study were 201 respondents and collected by purposive sampling method. The test was carried out using the Structural Equation Model (SEM) method. The independent variables in this study are CSR, Ethics, and Green Marketing. The dependent variable is Brand Image. In addition, the mediating variable is Brand Image. The results of this study are (1) CSR does not have a positive effect on Brand Image, (2) Ethics has a positive effect on Brand Image, (3) Green Marketing has a positive effect on Brand Image, (4) Brand Image has an effect positive towards Brand Loyalty.